Efek Residu Biochar Sekam Padi terhadap Pertumbuhan dan Hasil Kedelai - Suli Suswana; Dick Dick Maulana (Agrotechnology Research Journal, 2023)
Biochar is a carbon-rich solid material derived from the pyrolysis of agricultural residue biomass, which takes longer to decompose than the raw material biomass. Biochar has been observed to have agronomic benefits. Because of its persistence in the soil, biochar has the potential to extend its agronomic benefits. The purpose of this study was to obtain evidence that biochar has a longer effect so that its residual effect can increase the growth and yield of soybean. A series of pot experiments which included 4 consecutive plantings were carried out. The treatments consisting of: control; rice husk biochar (RHB) 20 ton.ha-1; RHB 40 ton.ha-1; RHB 50 ton.ha-1; RHB 60 ton.ha-1; RHB 10 ton.ha-1 + chicken manure (CM) 10 ton.ha-1; RBH 20 ton.ha-1 + CM 20 ton.ha-1; RHB 30 ton.ha-1 + CM 30 ton.ha-1. The treatments were applied to the first planting of the series experiment (September-December 2018). To determine the residual effect of the treatments, the second experiment was carried out in February-June 2019 with planting aerobic rice plants, third experiment in March-June 2020 with soybeans plant, and fourth experiment in July-October 2020 with soybean plants. The results showed that the effect of residual rice husk biochar did not significantly increase growth and soybean yields in the 3rd and 4th planting.